Bring Out the Bulls: Employment Dynamics of Trucking Firms During Highly Expansive Market Conditions - Jason W. Miller; Jonathan Phares; Stephen V. Burks (Institute of Labor Economics (IZA), 2025)
Studying employment dynamics (i.e., rates at which firms add or shed workers) of small- and medium-sized enterprises (SMEs) like trucking firms is critical to inform labor market theory and public policy. We examine U.S. trucking firm employment dynamics during the highly expansive period of March 2020 – March 2021, when the COVID-19 pandemic delivered an exogenous shock that upended established freight networks and sharply expanded demand. We extend the supply chain management (SCM) literature on motor carrier growth and Penrose's theory of the growth of the firm (TGF), focusing on the mechanisms most likely to be involved. We test our hypotheses using Business Dynamics data from the Census Bureau for the population of trucking firms with at least one employee. Fitting mixed effects models, we find that both the increase in job gains and decrease in job losses during March 2020 – March 2021 were greater for younger as compared to older firms, and the effect on job losses was greater in absolute magnitude. Our work modifies TGF with regard to SMEs that make up the bulk of firms in industries traditionally viewed as central to SCM, and it adds to evidence against a long-term or systematic shortage of truck drivers.
Keywords: J21; L92; R41; J63; 330; labor demand; driver shortage; motor carrier; trucking; public policy